Aquifer Barreiras: Evaluation of ground water reserves in northern Espírito Santo, southeastern Brazil - Gonçalves, José Augusto Costa; Vieira, Eliane Maria (International Journal of Advanced Engineering Research and Science, 2019)
The aquifer Barreiras is porous, free and semi-confined, with high porosity and permeability. It is composed of alluvial and fluvial sediments of the Barreiras Formation, in a complex association of permeable/impermeable strata. The mean hydrodynamic parameters of the 107 registered and evaluated tubular wells are a depth of 100.81 m, static level of 14.18 m, dynamic level of 51.48 m, drawdown of 37.30 m, a flow rate of 43.52 m, specific flow of 2,3681 m and transmissivity of 175.54 m2/day. The natural outflow of Barreiras Aquifer is 296.106 m3/year, the Infiltration Rate is 0.82%, the Regulatory Reserve or Recharge Volume 321.106 m3 and the Permanent Reserve volume 1,27.1010 m3. The hydrodynamic characteristics of the Aquifer Barreiras indicate a promising underground source and high heterogeneity throughout the formation.